Art to resist, writing to revolutionize : a quest for individual, social, and aesthetic transformation in Manual de pintura e caligrafia by José Saramago - Marilda Beijo Fróes; Daniel Vecchio Alves (Études romanes de Brno, 2025)
In this study, we conducted a literary analysis of José Saramago's Manual de Pintura e Caligrafia (1977), focusing on the narrative's setting during the historical period leading up to the Carnation Revolution on April 25, 1974, a revolutionary movement led by the military and supported by the population. In this context, a parallel is drawn between the transition from dictatorship to democracy and the shift from painting to calligraphy in the craft of the protagonist, H. This parallel highlights how his personal and aesthetical transformation unfolds alongside the country's liberation, marking the beginning of a new sociocultural and political era in Portugal. Thus, we conclude that the revolutionary moment depicted in the novel is not merely a distant historical event but is deeply intertwined with the internal development of the character H., aligning with the climax of his quest for freedom and artistic authenticity.